PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA PADA KINERJA GURU (STUDI PADA GURU SD PENERIMA TUNJANGAN PROFESI DI UPT DINPENDIK KECAMATAN KALIORI KABUPATEN REMBANG) - Suyanto, 1142020130; Tjahjaningsih, Endang (Jurnal Mahasiswa Pasca Sarjana, 2014)
The study specifically identified the link between compensation, motivation, and job satisfaction toward performance of Elementary School teachers received certification of Unit Pelaksana Teknis (UPT) Dinas Pendidikan Kecamatan Kaliori Kabupaten Rembang. The research employed questionnaire to collect data from respondents. Five research hypotheses were formulated and tested. The data used were primary data. Purposive sampling was used to select samples and Multiple Regressions Analysis was used to analysis the data with the aid of statistical package for social sciences (SPSS) version 16.00. The hypotheses indicated that there is no significant relationship between compensation variables with performance. There was significant relationship between compensation and motivation to job satisfaction. There were significant relationship between compensation and job satisfaction toward performance. The study recommends that job satisfaction should be a plank to determine their job satisfaction and tenure transparency Â should be emphasized rather than combination of salary and commission to enhance better performance. Keywords : Compensation, Motivation, Work Satisfaction, Performance Â